A new synthetic route for the preparation of pregabalin. Issue 13 (3rd July 2021) - He, Chasheng; Zhai, Ziran; Zhou, Yang; Li, Jianqi; Wang, Guan
Abstract: We reported the synthesis of (S)-pregabalin in a five-step sequence with 20% overall yield. As a modification of the previously developed route, a Michael addition between CH3 NO2 and chiral oxaoxazolidinone was employed as a key operation for introducing the methyleneamino group, which allowed avoiding the use of toxic cyanide reagent and led to enantiomerically pure product (>99% ee) after the recrystallization in appropriate solvent. Graphical Abstract: UF0001